Spiritual inclinations in post-pandemic travel - Kainthola, Snigdha; Robledo, Marco; Chowdhary, Nimit R. (Turyzm/Tourism, 2022)
The detrimental impact of the COVID-19 on the world has ensued unrest amongst people. The reverberations of the life-threatening virus are conspicuous in all realms of life culminating in physical and psychological disturbance. The fear of loss of life, threatened livelihood and enforced seclusion has resulted in psychological morbidities. The existing literature demonstrates the positive effects of spirituality and religion in the life of someone mentally ailing as an efficient way of coping with problems. Spirituality is believed to provide positive emotions such as hope, courage and perspective to individuals. The current article based on a review of the literature highlights the burgeoning of post-pandemic spiritually-inclined travel to restore the balance of life. It adds to current knowledge on the effect of the pandemic on the human psyche and the mitigating effects of spirituality. The results also allow better marketing, management, and design techniques for the spiritual tourism product by providing knowledge on tourist behaviour post-pandemic. The conclusions from the review aim to evoke governments to accord more attention towards the mental health of individuals and advance programmes to help the distressed.